PENGARUH MODAL KERJA TERHADAP LIKUIDITAS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hikmah, Nurul Nurul (EKONOMIA, 2019)
The formulation of the problem in the increase in cash turnover, receivable turnover, inventory turnover and working capital turnover in pharmaceutical companies listed on Indonesia Stock Exchange for the period 2014-2016.      The theoretical basic for this research is financial management which focuses on working capital which consists of cash turnover, accounts receivable turnover, inventory turnover and liquidity ratio. the analytical tool used is cash turnover accounts receivable turnover, inventory turnover and liquidity.      The hypothesis in this study is an increase in cash turnover, inventory turnover and working capital turnover followed by an increase in liquidity (current ratio) in pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2014-2016.      The results of this study stated that the increased in cash turnover was not accompanied by an increase in liquidity in pharmaceutical companies listed on the indonesia stock exchange in 2014-2016 the hypothesis was rejected. The increase in receivable turnover is not accompanied by an increase in liquidity in pharmaceutical companies listed on the indonesia stock exchange in 2014-2016 hypothesis was rejected. The increase in inventory turnover wasn’t accompanied by an increase in liquidity in pharmaceutical companies listed on the indonesia stock exchange in 2014-2016 hypothesis was rejected. The increase in working capital turnover wasn’t accompanied by an increase in liquidity in pharmaceutical companies listed on the indonesia stock exchange in 2014-2016 hypothesis was rejected.